China : From Afforestation to Poverty Alleviation and Natural Forest Management - Rozelle, Scott; Huang, Jikun; Husain, Syed Arif; Zazueta, Aaron (Washington, DC: World Bank, 2014)
This case study is one of six evaluations of the implementation of the World Bank's 1991 Forest Strategy. This and the other cases (Brazil, Cameroon, Costa Rica, India, and Indonesia) complement a review of the entire set of lending and nonlending activities of the World Bank Group and the Global Environment Facility. This OED study finds that while China's forest program was highly successful, much remains to be done. Too little is known, for example, about the distribution of benefits between households and production and marketing units. The implications of the recent logging ban require careful analysis. Policy reforms, particularly for state-owned enterprises, must still be completed. Data on what is happening in China's forests is inadequate to support a firm judgment, particularly regarding the country's natural forests. There is almost a complete absence of systematic knowledge about the nation's current stock and future trends of the supply, demand, marketing, and trade for timber and some key non-timber products. Finally China has graduated from IDA funding to IBRD lending, a prospect believed to have serious consequences for the most innovative aspect of China's program, a "responsibility system," that ensures a high level of ownership for the protection of the country's forests. In addition, recent controversies regarding the treatment of indigenous peoples in Xizang are already increasing risks for the Bank's new style forest sector investments, which have tended to focus on the poorest mountain populations, many of which include ethnic minorities.